OP72 Being alone together: a longitudinal dyadic analysis on the impact of loneliness and relationship quality on wellbeing in couples coping with disability. (September 2018) - Tough, H; Brinkhof, MWG; Siegrist, J; Fekete, C
Abstract : Background: Couples coping with disability are at an increased risk of experiencing poor wellbeing, this may be due to the potentially harmful effects of loneliness and poor relationship quality that this population are frequently exposed to. Both loneliness and poor relationship quality have profoundly detrimental effects on health and wellbeing. The experiences of loneliness and poor relationship quality are though to a elicit a stress response, which when experienced chronically, can result in behavioural biases and negative physical and mental health outcomes. In comparison, the experience of high quality relationships can buffer the negative effects of other external stressors. To date, little is known about how the perceptions of loneliness and relationship quality within couples coping with a disability affect wellbeing, or how the partners' perceptions of loneliness and relationship quality affect the individuals' wellbeing, furthermore the directionality of effect is not well understood. Methods: In this study, we investigate the actor and partner effects, and the reciprocal effects of loneliness and relationship quality on wellbeing. The analyses are based on longitudinal dyadic data from the pro-WELL study (n=246), a Swiss community survey of persons with spinal cord injury (SCI) and their partners. Data was collected over a 12 month period using telephone interviews and questionnaires. We employed mixed effects modelling to explore actor and partner effects, and used cross-lagged path analysis to explore reciprocal effects. Both of these analyses were stratified to account for the potential differential effects in persons with SCI and their caregiving partners. Results: We found loneliness to be more prevalent in persons with SCI compared to their caregiving partners. Caregiving partners were found to be more sensitive to their own, and their partners' experiences of relationship quality, as we found significant actor effects ( β =0.15 CI:0.04, 0.26), and significant partner effects of relationship quality on wellbeing ( β =0.21 CI:0.10, 0.32). In both persons with SCI ( β =−0.30 CI:−0.41, –0.18) and their caregiving ( β =−0.20 CI:−0.31, –0.10), we found significant actor effects of loneliness on wellbeing. Over time, loneliness demonstrated reciprocal associations with wellbeing, as did relationship quality in caregiving partners, indicating a possible cycle of positive development between reducing loneliness, improving relationship quality and enhancing wellbeing. Conclusion: The findings of our study emphasise the high prevalence of loneliness in persons with SCI and the importance of reducing loneliness and strengthening relationship quality in order to improve wellbeing in couples coping with disability.